Procedural Generation of Isometric Racetracks Using Chain Code for Racing Games - Nascimento, Erik Jhones F. do; Castro, Tassiana M.; Abreu, Ana Carolina S.; Lira, Filipe A.; Souza, Amauri H. (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2021: Anais do XX Simpósio Brasileiro de Jogos e Entretenimento Digital, 2021)
In this work, we propose a procedural generation method for railroad circuits based on the chain code algorithm.The process creates a list with directions in a two-dimensional space from a series of operations using the chain code and imagesof predefined real tracks. This list was used in the Unity engine to provide the positions, starting from a predefined starting point, which will insert the elements of the circuit during its creation. The race track format still goes through a preprocessing method to filter the ladder effect generated by the chain code andfine-tune details before being simulated in a game. This allow seach track to have a unique pattern and good gameplay. Testscarried out using our generation method in a 2D (two dimensions) isometric kart game showed that in all runs, the tracks had anaverage of 98.5% difference among them and maintained the gameplay standards.